Phytohabitans kaempferiae sp. nov., an endophytic actinomycete isolated from the leaf of Kaempferia larsenii - Nantawan Niemhom; Chanikul Chutrakul; Chanwit Suriyachadkun; Chitti Thawai (My University, 2016)
A novel endophytic actinomycete, designated strain KK1-3T, which formed single spores and long chains of spores (more than 10 spores) was isolated from surface-sterilized Kaempferia larsenii leaf collected from Ubon Ratchathani province, Thailand. The isolate contained l-lysine, meso-diaminopimelic acid and hydroxyl diaminopimelic acid in the cell-wall peptidoglycan. The whole-cell sugars included glucose, mannose, rhamnose, ribose, galactose and xylose. The characteristic phospholipids were phosphatidylethanolamine, phosphatidylmethylethanolamine, phosphatidylglycerol, diphosphatidylglycerol, phosphatidylinositol and phosphoglycolipids. The predominant menaquinones were MK-10(H8), MK-10(H6) and MK-10(H4). The predominant cellular fatty acids were anteiso-C17 : 0 and iso-C16 : 0. The G+C content of the genomic DNA was 71 mol%. Phylogenetic analysis using 16S rRNA gene sequences revealed that strain KK1-3T should be classified as representing a member of the genus Phytohabitans. The similarity values of sequences between this strain and those of the closely related species, Phytohabitans houttuyneae K11-0057T (99.0 %), Phytohabitans suffuscus K07-0523T (98.9 %), Phytohabitans flavus K09-0627T (98.6 %) and Phytohabitans rumicisK11-0047T (98.1 %) were observed. The DNA-DNA hybridization result and some physiological and biochemical properties indicated that KK1-3T could be readily distinguished from its closest phylogenetic relatives. On the basis of these phenotypic and genotypic data, this strain represents a novel species, for which the name Phytohabitans kaempferiae sp. nov. is proposed. The type strain is strain KK1-3T (=BCC 66360T =NBRC 110005T).
Keywords: Plant and Fungal Species Descriptions